La literatura infantil en el desarrollo de la creatividad en los estudiantes del séptimo año de educación básica, paralelo A de la escuela Simón Bolívar de la ciudad de Riobamba, Provincia de Chimborazo período 2014-2015 - Montalvo Rodríguez, Alejandra Carolina (2016)
This research arises from the need to help in the development of the imagination in children of the seventh year of basic education in the Simon Bolivar School, as there is a poor use of Children’s literature. The objective pursued is to determine the incidence of children’s literature in the development of creativity; to reach their fulfillment we rely on the theoretical framework that is the basis f the research, so we appropriated children’s literature with diversity and creativity. It is proposed a hypothesis that after the analysis and interpretation of results, depending on the percentage method lets us see that children’s literature affects the development of creativity. In the methodology we take possession of the non-experimental design because it has not been tampered with any variable, the types of research were descriptive and explanatory causal and type of study: transversal, the methods used were scientific, inductive, deductive analytical and synthetic, the same that guided the research work. The population was 27 subjects divided into strata 27 boys and 10 girls so there was closed – end alternative selection. With relevant findings of this research an alternative proposal which improves the development of creativity through strategies was developed. It is concluded on the need to implement this proposal